ADOLESCENTS MENTAL HEALTH DURING COVID-19 PANDEMIC - Rahmayanthi, Denia; Moeliono, Marisa Fransiska; Kendhawati, Lenny (Insight: Jurnal Ilmiah Psikologi, 2021)
Since the end of 2019, the Covid-19 pandemic has been experienced in various countries, including Indonesia. The existence of measures to prevent the spread of the Covid-19 has an impact on physical activity and policies on implementing Distance Learning (PJJ) for students ranging from elementary school to college levels. The purpose of this study was to obtain an overview of the mental health of adolescents during the Covid-19 pandemic and the sociodemographic factors that influence adolescent mental health. The study involved 205 participants aged 15-18 years. The data were collected using a validated General Health Questionnaire (GHQ-12) self-assessment measurement tool in Indonesia. The results showed that 59.5% of adolescents experienced psychological problems in the form of psychological distress and social dysfunction. Girls and adolescents who experience changes in sleep hours have a greater tendency to experience psychological problems. So that during the pandemic, teenage girls need more attention than boys, sleep patterns also need to be considered so as not to have an impact on psychological distress and social dysfunction during the pandemic.